PENERAPAN KAMUS GEOGRAFI BERBASIS BOT TELEGRAM UNTUK MENINGKATKAN LITERASI SISWA DALAM MEMAHAMI MATERI FENOMENA GEOSFER SUB BAB LITOSFER - Ikhlasul, Galih; Murtini, Sri; Rindawati, Rindawati (Jurnal Pendidikan : Riset dan Konseptual, 2025)
This study aims to develop and assess the effectiveness of implementing a Telegram Bot-based Geography Dictionary in enhancing students' geographical literacy, specifically in understanding Lithosphere material. The method used was a quasi-experimental design with a non-equivalent control group, involving two groups: an experimental group that utilized the Telegram Bot as a learning medium and a control group that used PowerPoint as a medium. The research results indicate that the application of the Telegram Bot as an interactive learning medium significantly improved students' geographical literacy. In the pre-test, the experimental group obtained an average score of 59.11%, while the control group scored 58.63%. However, after the implementation of the Telegram Bot medium, the experimental group experienced a higher increase, with post-test scores reaching 76.56%, whereas the control group only recorded a score of 67.89%. An independent T-test revealed a significant difference between the two groups (p < 0.05), confirming that the use of the Telegram Bot had a greater impact on improving students' geographical literacy. Media validation results by material experts and media experts also showed that this medium is highly suitable for use in the geography learning process. Based on these findings, it can be concluded that the Telegram Bot-based Geography Dictionary is an effective and viable medium for enhancing students' understanding of Lithosphere material and can be implemented in geography learning in secondary schools.